Implementasi Metode Spiral dalam Pengembangan Sistem Informasi Penerimaan Peserta Didik Baru Berbasis Web - hidayat, husni (JATISI, 2025)
SMK Ma'arif NU Doro is a private school in Pekalongan Regency. This school faces challenges in the New Student Admission (PPDB) process. With the conventional method, the registration process for prospective new students is less than optimal because it does not yet use a web-based registration system. Therefore, this research aims to implement the spiral method in developing a web-based PPDB system. The development is carried out incrementally, allowing flexibility and adaptability to changes. Each stage of development adds new features until the system is complete. The research results show that the spiral method is suitable for use because it provides room for adjustments according to needs to improve the efficiency and quality of the PPDB process at SMK Ma'arif NU Doro